Multidomain SDN-Based Gateways and Border Gateway Protocol. (12th May 2022) - Alotaibi, Hamad Saud; Gregory, Mark A.; Li, Shuo
Abstract : The Internet consists of distributed and interconnected autonomous systems (ASs). The flexibility afforded by the Internet architecture ensures that timely changes to the network topology can occur without centralized control. The Border Gateway Protocol (BGP) is an Internet protocol that routes the Internet traffic and exchanges the information between AS. However, BGP version 4 (BGP-4) currently suffers from a limitation called "high convergence delay" while doing routing updates, which is a very common limitation, damaging the performance of contemporary IP networks. Software-defined networking (SDN) was conceived at the beginning of the 21st century, and over the intervening years, it has gained traction. This technology has significantly enhanced traffic control, management, and monitoring, particularly in data centres and enterprise networks. Challenges have been found including how to provide administrative control, security, management, and monitoring at domain boundaries while introducing the SDN paradigm. In multidomain SDN, BGP-4 is used to exchange the information and route the traffic between domains or diverse AS. In this review, an investigation is provided on using the SDN paradigm to enhance multidomain traffic management and control and to optimize BGP operation. A detailed insight is provided into the penetration of the SDN paradigm into modern networking architectures and how it may help in facilitating future research to improve BGP-4.